Stakeholder perceptions on women’s health after obstetric fistula repair: results from a qualitative study in Guinea - Delamou, Alexandre; Delvaux, Thérèse; Diallo, Aissatou; Douno, Moussa; Dialo, Moustapha; De Brouwere, Vincent; Diop, Altine; Tripathi, Vandana; Romanzi, Lauri (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To explore stakeholder perceptions on the health of women after female genital fistula repair in Guinea. Methods: In-depth interviews (IDIs) and focus group discussions (FGDs) were conducted with stakeholders involved in fistula prevention and management in Conakry, Labé and Kissidougou regions, where EngenderHealth supports fistula repair hospitals. Results: 41 IDIs and seven FGDs (with 42 participants) were conducted with various stakeholders. Women who underwent fistula surgery and were discharged with a closed fistula were described as carrying several health risks. These women are seen as people more exposed to maternal and neonatal complications during pregnancy and childbirth than women who do not experience fistula. The core category that emerged to describe women treated for fistula was “vulnerability”. Women treated for fistula were described as “vulnerable” as compared to “normal” women who have never experienced fistula. The concept of “vulnerability” included physical, social (including mental) and economic dimensions. Physical vulnerability included the sequalae of the condition and the risk of maternal and neonatal complications such as fistula recurrence, abortion or stillbirth. Social vulnerability that includes mental vulnerability was described through the continuous stigmatization of women, the social pressure to fulfil marital duties i.e. resuming sexual intercourse or becoming pregnant again. Economic vulnerability included poverty related characteristics, lack of autonomy that maintain financial barriers to access health care. Conclusions: Fistula care should go beyond surgery by developing and implementing interventions that address women’s physical, psychosocial and economic vulnerabilities.